Penentuan industri kecil pangan unggulan dengan metode SAW dan dampaknya terhadap daya serap tenaga kerja di Kota Jambi - Yuvanda, Sesraria; Aisyah RJ Nur, Deby (Jurnal Paradigma Ekonomika, 2021)
Small and Medium Industry (SMI) have an important role in economic development to increase the value of products and providing employment as an industry. The purposes of this research are to determine the leading sector of food small-industry in Jambi City, and to measure the contribution rate of it in absorb labors within the city. The result showed that in Jambi City, the leading sector of food small-industry was a group of nut-processing industry and plantation product-processing industry. That leading sector contributed 18.65 percent to the absorption of labor. Â